Reformulating Modalism - (:unkn) unknown (My University, 2016)
In accounting for something’s essence, the features it must have are good candidates for being essential to it. Call this view modalism. Kit Fine (1994) raises some objections to modalism, and I respond by reformulating it in a way that avoids those objections. My reformulation makes use of grounding identities, and it is on better footing than two recent reformulations of modalism by Nathan Wildman (2013) and David Denby (2014). The claim that something grounds a thing’s identity is controversial, and so I develop an argument for it showing that the identities of things are grounded in either qualitative features, non-qualitative features, or nothing at all. And it turns out that identities being grounded in either non-qualitative features or nothing at all is implausible. So, identities are grounded in qualitative features, and the qualitative features that ground a thing’s identity are the ones essential to it.
Keywords: Grounding; Grounding Identities; Kit Fine; Modalism